ANALISIS KELAYAKAN USAHA KOPRA PUTIH DENGAN SISTEM PENGOLAHAN GREEN HOUSE DAN PROSPEK PENGEMBANGANNYA PADA MASYARAKAT TANI KECAMATAN KULISUSU UTARA KABUPATEN BUTON UTARA - Muhammad Fajar Yudha Febriansyah; La Nalefo; Musadar Musadar (Fakultas Pertanian Universitas Halu Oleo, 2022)
Copra is the white flesh of the coconut fruit which is dried in the sun or using artificial heat for several days so that it can become copra. The prospect of developing white copra business has a fairly high opportunity because the agricultural and plantation sectors in Indonesia still play an important role as one of the pillars of national economic growth, this has an impact on increasing people's economic empowerment and improving people's living standards. well-being. This study aims to (1) how much income is used by white copra business actors for the greenhouse system in North Kulisususu Regency, North Buton Regency. (2) how is the feasibility of white copra business actors with a greenhouse system in North Kulisusu Regency, North Buton Regency. (3) What is the strategy for developing white copra farming with a greenhouse system in North Kulisususu District, North Buton Regency. The sample in this study were 3 people who isolated white copra with a greenhouse system. The data analysis used is income analysis, R/C ratio for business feasibility and descriptive data analysis for business development strategy. Based on the results of the research, the income of the white copra processing business with the green house system from the three respondents averaged after Rp. 20,146,611 Overall the average eligibility score of the three respondents is 1.3. Based on the results of the research above, the three respondents have a feasibility value > 1 so that the white copra processing business in the research location is worth trying. Thus, the white copra processing business in North Kulisusu District is feasible to be developed. In developing the white copra processing business, there are several efforts or strategies that must be carried out, including: distribution/channeling strategy, price strategy/price competition and capital strategy.